Longitudinal changes in physiological factors associated with dietary behaviour in J-League U-15 football players - Sugiura, K.; Shibata, U.; Sanbongi, C.; Ohta, A.; Sakai, K. (7th World Congress on Science and Football (WCSF), 2011, 2011)
In elite youth football players, the psychological predictors of proper diet implementation were identified in a cross-sectional study (Shibata U. et al.). The aim of this study was to confirm these relationships via longitudinal observation. Methods Eight hundred and seventy U-15 football players in the J-league completed self-administered questionnaires and 3-day food records in Nov. 2007 (T1) and Sept. 2008 (T2). Subsequently, all subjects were divided into three groups: forward stage transition from T1 to T2 (G1), no stage transition (G2), and backward stage transition from T1 to T2 (G3). Results & Discussion There was a significant difference in the stage of change distribution between T1 and T2 (p=0.006). Positive perceptions (pros), self-efficacy, social support, and behavioral skills in G1 were significantly higher compared to G3. Negative perceptions (cons) in G1 were lower compared to G3. Moreover, intake of calories, carbohydrate, protein, calcium, iron, and vitamins A, B1, and B2 in G3 were significantly higher compared to G1. Our results suggest that decisional balance, self-efficacy, and social support scores might be effective predictors of stage transition. Conclusion The results of this study employing longitudinal observation were consistent with the results of the cross-sectional study.